Modeling the contraction of the pelvic floor muscles. Issue 4 (11th March 2016) - Brandão, Fernanda Sofia Quintela da Silva; Parente, Marco Paulo Lages; Rocha, Paulo Alexandre Gomes Gonçalves; Saraiva, Maria Teresa da Quinta e Costa de Mascarenhas; Ramos, Isabel Maria Amorim Pereira; Natal Jorge, Renato Manuel
Abstract : We performed numerical simulation of voluntary contraction of the pelvic floor muscles to evaluate the resulting displacements of the organs and muscles. Structures were segmented in Magnetic Resonance (MR) images. Different material properties and constitutive models were attributed. The Finite Element Method was applied, and displacements were compared with dynamic MRI findings. Numerical simulation showed muscle magnitude displacement ranging from 0 to 7.9 mm, more evident in the posterior area. Accordingly, the anorectum moved more than the uterus and bladder. Dynamic MRI showed less 0.2 mm and 4.1 mm muscle dislocation in the anterior and cranial directions, respectively. Applications of this model include evaluating muscle impairment, subject-specific mesh implant planning, or effectiveness of rehabilitation.